2000
DOI: 10.1038/modpathol.3880231
|View full text |Cite
|
Sign up to set email alerts
|

Expression of p53 and PCNA in Cholangiocarcinoma and Primary Sclerosing Cholangitis

Abstract: The aim of this study was to identify the pattern and significance of expression of p53 and PCNA in cholangiocarcinoma and primary sclerosing cholangitis. Histological sections from 18 patients with cholangiocarcinoma (3 of the cases were associated with primary sclerosing cholangitis), 10 patients with primary sclerosing cholangitis without cholangiocarcinoma, and 7 patients with cirrhosis without cholangiocarcinoma or primary sclerosing cholangitis were stained immunohistochemically for p53 and PCNA. Samples… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 7 publications
4
21
0
Order By: Relevance
“…Of the 282 genes identified as overexpressed threefold or greater in biliary cancers, only three have been reported previously in the specific context of biliary cancers. [41][42][43] Thus, this study has enormous potential in terms of expanding our knowledge of biliary cancer pathogenesis and identification of novel cellular targets in this cancer type. In addition to using the recently developed Affymetrix U133A microarray that probes for ϳ22,000 transcripts on a single platform, other methodological strengths of our study include the use of a large number of biliary cancer cell lines representing different sites in the biliary tree, verification of neoplastic cellularity of primary resected cancers using frozen section examination, and the appropriate use of enriched biliary epithelium (as opposed to "full thickness" biliary ductal sections) as controls for comparison of gene expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 282 genes identified as overexpressed threefold or greater in biliary cancers, only three have been reported previously in the specific context of biliary cancers. [41][42][43] Thus, this study has enormous potential in terms of expanding our knowledge of biliary cancer pathogenesis and identification of novel cellular targets in this cancer type. In addition to using the recently developed Affymetrix U133A microarray that probes for ϳ22,000 transcripts on a single platform, other methodological strengths of our study include the use of a large number of biliary cancer cell lines representing different sites in the biliary tree, verification of neoplastic cellularity of primary resected cancers using frozen section examination, and the appropriate use of enriched biliary epithelium (as opposed to "full thickness" biliary ductal sections) as controls for comparison of gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…A second PubMed search using the gene name and either "cholangiocarcinoma," "biliary," "bile duct," or "gallbladder" in the text search revealed that only three up-regulated genes (hepatocyte growth factor, proliferating cell nuclear antigen, and cytosolic phospholipase A2) have been previously reported as specifically overexpressed in biliary cancers. [41][42][43] Thus, the overwhelming majority of up-regulated genes reported in this study represent novel tumor markers and cellular targets for this cancer type.…”
Section: Identification Of Differentially Up-regulated Genes In Biliamentioning
confidence: 99%
“…First, RAR␥ plays an active role in promoting cell proliferation and tumorigenicity, enhancing migration and invasion, and inducing multidrug resistance of CCA cells. Second, RAR␥ facilitated the G 1 /S transition; regulated P21 and cyclin D1, two critical cell cycle regulators (27); and upregulated the expression of the proliferation marker PCNA (28), which may contribute to tumor growth. Third, CCA is characterized by early metastasis (1), in which MMP-9 plays a critical role (29).…”
Section: Discussionmentioning
confidence: 99%
“…Cancer-relevant mutations involving p53 have been reported at different frequencies ranging from 10% to 50% of all intrahepatic CCA cases (18)(19)(20). Abnormal nuclear accumulation of p53 has also been reported in human intrahepatic CCA (21)(22)(23)(24)(25) and attributed to either p53 mutation or ill-defined epigenetic regulation possibly involving MDM2 (18,19). Mutations in p53 have been detected in advanced disease; however, increased p53 expression in dysplastic lesions and adjacent nonneoplastic bile duct epithelium has suggested a possible role for p53 dysregulation during the formative stages of intrahepatic CCA development (25).…”
Section: Introductionmentioning
confidence: 99%